Clinical And Immunological Outcomes Of A National Paediatric Cohort Receiving Combination Antiretroviral Therapy In Uganda - Kiboneka, Andrew; Wangisi, Jonathan; Nabiryo, Christine; Tembe, Juliet; Kusemererwa, Sylvia; Olupot, Peter Olupot; Joffres, Michel; Anema, Aranka; Cooper, Curtis L.; Montaner, Julio S.; Mills, Edward J. (Aids, 2008)
We aimed to evaluate clinical and immunological outcomes of paediatric patients receiving combination antiretroviral therapy (cART) enrolled in The AIDS Support Organization (TASO) Uganda national HIV/AIDS programme.Observational study of patients (age <14 years) enrolled in 10 clinics across Uganda for which TASO has data.We extracted patient demographic, immunological and clinical outcomes from the TASO databases regarding age, sex, cART regimen, CD4 cell count and WHO stage at initiation, tuberculosis, mortality and adherence. Outcomes were analysed using Pearson's rank–order correlations, Wilcoxon's rank sum tests, Cox proportional hazard model and survivor functions.Of the total 770 HIV children on cART, median age was 9 years (interquartile range, 5–13 years), and median follow-up time was 377 days (interquartile range, 173–624 days). Seven hundred and fifty-one children (97.5%) initiated nonnucleoside reverse transcriptase inhibitor-based regimens. Three hundred and sixty-five children (47.5%) initiated cART with severe immune suppression (CD4 cell percentage <15). Of the 18 (2.3%) children that died, mortality was associated with lower CD4 cell percentage at initiation (B coefficient −0.144, standard error 0.06, P = 0.02). Of the total, 229 (30%) were single or double orphans and more likely to initiate cART at an older age (mean age, 9.25 vs. 8.35 years, P = 0.02) and have a lower CD4 cell count (median, 268 vs. 422 cells/μl, P ≤ 0.0001) and CD4 cell percentage (median 12.8 vs. 15.5%, P = 0.02) at initiation. Pulmonary tuberculosis was present in 43 (5.6%) patients at initiation and 21 (2.3%) after cART. Almost all patients (94.9%) demonstrated more than 95% adherence.Children on cART in Uganda demonstrate positive clinical outcomes. However, additional support is required to ensure timely cART access among orphans and young children.
Keywords: Africa, children, HIV/AIDS, paediatrics